Strategi Pemerintah Daerah Kota Langsa Povinsi Aceh dalam Mengembangkan Obyek Wisata Halal - Iskandar Budiman; Safwan Kamal; Andi Tarlis (Jurnal Samudra Ekonomi dan Bisnis, 2020)
This study aims to determine the strategy of the Langsa City Government of Aceh Province in developing Halal tourism objects in Langsa City. This phenomenological research involved three key informants with interview, observation and documentation data collection techniques. This research identifies several strategies of the Langsa city government to develop halal tourism. First, realizing ideas from the regional head by considering the potential of the region and the local community. Second, realize ideas with sustainable and continuous development methods. Third, develop mangrove forests and urban forests as the main destination at this time, and multipurpose forests will be built in the future. Fourth, creating benefits for the community in the presence of halal tourist destinations. Fifth, guarantee all sharia-based tourism and be protected from things that violate the norms and ethics and customs of the community. Sixth, do promotions with various social media and print and take part in the Indonesian Enchantment event and other national and international level activities to market halal tourist destinations. Seventh, building public awareness to get used to glorifying tourists.